2020
DOI: 10.1089/neu.2020.6993
|View full text |Cite
|
Sign up to set email alerts
|

Serial Diffusion Kurtosis Magnetic Resonance Imaging Study during Acute, Subacute, and Recovery Periods after Sport-Related Concussion

Abstract: Sport-related concussion (SRC) is common in contact sports, but there remains a lack of reliable, unbiased biomarkers of brain injury and recovery. Although the symptoms of SRC generally resolve over a period of days to weeks, the lack of a biomarker impairs detection and return-to-play decisions. To this date, the pathophysiological recovery profile and relationships between brain changes and symptoms remained unclear. In the current study, diffusion kurtosis imaging (DKI) was used to monitor the effects of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…These findings are in line with a few previous studies reporting that DKI was superior to DTI in detecting deviations in white matter in the acute to chronic phase after MTBI. 33,35 The present results add to this literature by showing that although DKI metrics were affected acutely by the MTBI, the DTI metrics were more closely related to PPCS development.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…These findings are in line with a few previous studies reporting that DKI was superior to DTI in detecting deviations in white matter in the acute to chronic phase after MTBI. 33,35 The present results add to this literature by showing that although DKI metrics were affected acutely by the MTBI, the DTI metrics were more closely related to PPCS development.…”
Section: Discussionsupporting
confidence: 77%
“…In previous subacute and chronic studies, it varies in which white matter tracts differences are observed, but differences in these tracts, especially in the corpus callosum, are commonly reported. 5,6,9,10,12,52 In contrast to studies on mixedmechanism MTBI, studies on sports-related concussion have acquired acute MRI more frequently, and a few studies have reported associations between higher MD, AD and RD and symptoms, 53,54 but a lack of associations has also been reported 35,55 However, the symptoms were also assessed acutely in most studies on sports-related concussion, which makes it difficult to directly compare these findings with ours. Moreover, the variability in both age and injury mechanism is considerably larger in mixed-mechanism studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations